Drosophila Ionotropic Receptor 25a mediates circadian clock resetting by temperature - Chen, C; Buhl, E; Xu, M; Croset, V; Rees, J; Lilley, K; Benton, R; Hodge, J; Stanewsky, R (Nature Publishing Group, 2015)
Circadian clocks are endogenous timers adjusting behaviour and physiology with the solar day1 . Synchronized circadian clocks improve fitness2 and are crucial for our physical and mental wellbeing3 . Visual and non-visual photoreceptors are responsible for synchronizing circadian clocks to light4,5 , but clock-resetting is also achieved by alternating day and night temperatures with only 2–4 °C difference6–8. This temperature sensitivity is remarkable considering that the circadian clock period (~24 h) is largely independent of surrounding ambient temperatures1,8 . Here we show that Drosophila Ionotropic Receptor 25a (IR25a) is required for behavioural synchronization to low-amplitude temperature cycles. This channel is expressed in sensory neurons of internal stretch receptors previously implicated in temperature synchronization of the circadian clock9. IR25a is required for temperaturesynchronized clock protein oscillations in subsets of central clock neurons. Extracellular leg nerve recordings reveal temperatureand IR25a-dependent sensory responses, and IR25a misexpression confers temperature-dependent firing of heterologous neurons. We propose that IR25a is part of an input pathway to the circadian clock that detects small temperature differences. This pathway operates in the absence of known ‘hot’ and ‘cold’ sensors in the Drosophila antenna10,11, revealing the existence of novel periphery-to-brain temperature signalling channels